2016
DOI: 10.1080/19386362.2016.1193662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulphuric acid pollutant on the shear behaviour and strength of sandy soil and sand mixed with bentonite clay

Abstract: Mixture of sandy soil and bentonite clay can be used to seal the sanitary landfills and prevent the spread of leachate. Over time, this mixture may be subjected to different landfill contaminants, including acidic pollutants and shear strength variations. The objective of this research was to study the effects of sulphuric acid pollutant with pH values of 7, 3 and 1 on the shear behaviour and strength of clean sand and sand mixed with bentonite clay using common consolidated undrained triaxial tests. The tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…When the soil is eroded by acidic or alkaline pollutants (e.g., acid rain, industrial wastewaters, etc. ), its physicochemical and mechanical properties change accordingly, in terms of Atterberg limits [26][27][28], compressibility [29,30], and mechanical strength [26,27,[31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…When the soil is eroded by acidic or alkaline pollutants (e.g., acid rain, industrial wastewaters, etc. ), its physicochemical and mechanical properties change accordingly, in terms of Atterberg limits [26][27][28], compressibility [29,30], and mechanical strength [26,27,[31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Rahman and Nahar 58 also found that the direct shear strength increased with an increase in pH using the ammonia solution for granular soils. Hassanlourad et al 59 studied the effect of sulfuric acid with a different concentration on the shear strength of the sand–bentonite mixture. They found that although the shear strength of sandy soil decreased in acidic pH, the addition of sulfuric acid led to the higher strength of the sand–bentonite mixture at a pH of 3.…”
Section: Introductionmentioning
confidence: 99%
“…The study of acid concentration on the mechanical properties of soil is also carried out. Acid has a great influence on the mechanical properties of soil (Hassanlourad et al, 2017;Chavali and Ponnapureddy, 2018;Koupai et al, 2020). used the laboratory permeability test of undisturbed loess to study the permeability characteristics under the action of three kinds of acid erosion, found the influence of acid concentration on the permeability coefficient, and analyzes its mechanism from the perspective of microstructure changes.…”
Section: Introductionmentioning
confidence: 99%